The Effect of Applied Behavior Analysis Method on the Communication Skills of Children with Autism Viewed from Gender in Bontang City - Suprianto; Matulessy , Andik; Pascarini, Amanda (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study seeks to explore the impact of ABA (Applied Behavior Analysis) therapy on enhancing communication skills in children with autism. An experimental design involving pre-test and post-test assessments was utilized to measure changes in communication abilities before and after the ABA therapy intervention. Analysis with the Wilcoxon Signed Ranks Test revealed a notable improvement in communication skills among children with autism following the ABA therapy. Descriptive findings indicated that the average communication score at the pre-test was 27.75, while the post-test mean rose to 40.38, demonstrating a gain of 12.63 points. The Wilcoxon test produced a p-value of 0.012, which is below the typical significance threshold of 0.05, meaning the null hypothesis (H₀), which suggests no difference between pre-test and post-test, can be rejected. Thus, it can be concluded that ABA therapy has a significant positive impact on improving communication abilities in children with autism. Despite these encouraging results, the study's sample size is a limitation, and further research with larger samples and extended follow-up periods is required to deepen our understanding of ABA therapy's long-term effects.